Taking Charge of Maine’s Fiscal Fortunes: Taxes are Only One Piece of the Puzzle - LaPlante, Josephine (Maine Policy Review, 1997)
Are Maine’s taxes too high? This question and others continue to plague policymakers and citizens throughout Maine. This article provides the first of two perspectives on how to achieve meaningful tax reform. Josephine LaPlante suggests taking the long view, evaluating carefully the state’s tax structure and the impacts of any tax reforms. She presents a comprehensive framework for considering such changes and argues that taking charge of Maine’s fiscal house includes not only tax reform but also a reassessment of how the state provides public services to meet the needs and preferences of its citizens.